Binding of a nuclear factor to a regulatory sequence in the promoter of the mouse H-2Kb class I major histocompatibility gene. - Baldwin, A S (1987)
A cis-acting regulatory sequence was identified upstream of the mouse H-2Kb class I major histocompatibility gene. Deletions in the H-2Kb promoter revealed that sequences located between 190 and 138 nucleotides upstream of the transcription initiation site contribute to basal gene expression as well as to stimulation by alpha-interferon. Furthermore, a nuclear factor found in several cell types binds with high affinity to a sequence centered 166 nucleotides upstream of the H-2Kb initiation site. In vivo competition experiments demonstrated that this factor plays a direct role in H-2Kb expression in mouse fibroblasts. The binding site for this factor is TGGGGATTCCCCA, a sequence of perfect dyad symmetry. This factor also binds a similar sequence in the 72-base-pair repeat enhancer element of simian virus 40.